Use of BRAF V600E as a Molecular Marker in Aggressive Colorectal Cancer - Bethy S Hernowo; Fenny Ariyanni; Sri Suryanti; Abdul H Hassan (Acta Medica Indonesiana)
Aim: to compare the immunoexpression of BRAF V600E among stage of colorectal cancer. Methods: this was a cross sectional, and retrospective study involving Dukes’ stage A, B, and C colorectal carcinoma, each with 15 cases. Immunohistochemistry was performed in paraffin-embedded specimens of tumor mass for the assessment of BRAF V600E. The proportion differences of immunoexpression of BRAF V600E among Dukes’stage A, B, and C were tested using Chi-Square test. Results: the result of positive BRAF V600E immunoexpression (moderately to strongly positive) in Dukes’stage A, B, and C were found in 1 of 15 cases, 4 of 15 cases and 13 of 15 cases respectively. BRAF V600E immunoexpression was statistically significant more frequent in Dukes’stage C (p<0,001, Chi-Square test). Conclusion: positive BRAF V600E immunoexpression could be used as a marker of aggresive colorectal carcinoma.